2016
DOI: 10.1111/bcp.13054
|View full text |Cite
|
Sign up to set email alerts
|

Drug disposition before and after gastric bypass: fenofibrate and posaconazole

Abstract: The disposition of fenofibrate was not altered after RYGB, whereas the oral disposition of posaconazole was significantly decreased following RYGB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 33 publications
0
31
0
Order By: Relevance
“…RYGBP was the predominant surgical procedure (n = 18) . In one study, BPD was investigated as the surgical procedure, while two studies investigated BPD‐DS, six studied SG, and one included jejunoileostomy …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…RYGBP was the predominant surgical procedure (n = 18) . In one study, BPD was investigated as the surgical procedure, while two studies investigated BPD‐DS, six studied SG, and one included jejunoileostomy …”
Section: Resultsmentioning
confidence: 99%
“…To investigate the consequence of delayed contact with bile salts after surgery, fenofibrate can be used as a model drug because its solubility is highly dependent on bile salt concentrations, while posaconazole dissolution is pH dependent and can thus be used to indicate the effect of increased gastric pH following surgery . The results showed that the disposition of fenofibrate remained unaltered, whereas the exposure of posaconazole was reduced following surgery . A substrate less dependent on bile acids for its absorption would have been expected to show an increased absorption rate, but since the contact with bile acids is delayed after RYGBP, the accelerated gastric emptying time had a less visible effect on a substrate such as fenofibrate.…”
Section: Resultsmentioning
confidence: 99%
“…Of the total 21 studies, some conducted more than one procedure: 19 studies investigated RYGB, five investigated SG, two investigated BPD‐DS, and one study investigated mini‐GB . The number of participants in these studies ranged from five patients in a single study to a maximum of 34 patients.…”
Section: Resultsmentioning
confidence: 99%
“…The drugs investigated in this review were benzodiazepines: midazolam; anti‐arrhythmics: digoxin; corticosteroids: hydrocortisone; hormonal: desogestrel; antidepressants: venlafaxine, escitalopram, duloxetine, citalopram, and sertraline; antihypertensives: metoprolol; lipid‐reducing drugs: fenofibrate, and atorvastatin; anti‐infectives: posaconazole, amoxicillin, and linezolid; analgesics: morphine, and paracetamol; anticoagulant: rivaroxaban; and antiplatelet: aspirin; and acid‐reducing drugs: omeprazole . Amouyal et al included drugs for treatment of human immunodeficiency virus (HIV), namely, the combinations of the antiretroviral drugs: abacavir, atazanavir, efavirenz, emtricitabine, lamivudine, darunavir, raltegravir, ritonavir, and tenofovir …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation